Effect of Non-Surgical Periodontal Therapy on the Serum Sialic Acid Levels in Diabetic Patients with Periodontitis - Suresh, Reshma; Jayachandran, Perayil; Fenol, Angel; Biswas, Raja; Krishnan, Sajitha; Kumar, K Aswini; Divakar, Darshan Devang; Vellappally, Sajith (Acta medica (Hradec Kralove), 2019)
Sialic acid (SA), a family of acetylated derivatives of neuraminic acid, an acute phase reactant by itself. It usually occurs as a terminal component at the non-reducing end of carbohydrate chains of glycoproteins and glycolipids. SA participates in multiple physiological functions, such as cell-to-cell interactions, cell migration and proliferation. Diabetes mellitus (DM) is a chronic metabolic disorder characterized by rise in blood glucose level. Periodontitis is a chronic inflammatory disease of the periodontal tissue, leading to destruction of bone surrounding the tooth and ultimately tooth loss. There is a two way relationship between diabetes mellitus and periodontitis. Periodontitis is the sixth complication of diabetes along with retinopathy, nephropathy, neuropathy, macrovascular disease, and altered wound healing. Inflammatory mediators like interleukin-6 and tumor necrosis factor-alpha produced during periodontal inflammation can interfere with the actions of insulin receptors and worsen the glycemic control of diabetic patients. Periodontitis is a major cause of tooth loss, affecting over 300 million people and bacteria associated with periodontitis are also linked with systemic problems like endocarditis, atherosclerosis. Recent work has highlighted a major role for the host sugar sialic acid in the biofilm physiology and host-pathogen interactions of T. forsithya, a key periodontal pathogen. There exists a need for a biomarker, for early detection of disease evolution and more robust therapy efficacy measurements. Serum sialic acids were estimated in Indian population by diphenylamine method and Thiobarbituric acid method. The average values were 68 ± 2.6 mg percent by DPA method and 56 ± 5 mg percent by TBA (thiobarbituric acid assay) method. Age and sex showed no influence on serum sialic acid level. Objectives of the present study was to compare (TSSA) level in healthy subjects, subjects with (CMP) with and without (NIDDM) and its effect on non-surgical periodontal therapy. In the present study, the participants were divided into three groups: Group A, B and C. Group A consists of systemically healthy subjects, Group B consists of subjects with (CMP) while Group C consists of subjects with (CMP) with (NIDDM) and results of this study indicated that, at baseline, there were significant differences between Group A, B and Group C with respect to all the clinical parameters, including (GI), (OHI-S), (PPD), (CAL), (TSSA) and (HbA1c) levels. Thus (TSSA) level could be considered as novel biomarker in the progression of periodontal disease and diabetic status. Periodontitis could be considered as a potential, modifiable, and independent risk factor for the development of diabetes. Early detection of elevated (TSSA) level may help in interpreting the progression of periodontitis, risk of development of diabetes mellitus in future and also to prevent complications.
Keywords: total serum sialic acid; Diabetes Mellitus, Type 2; lidé středního věku; lidé; ženské pohlaví; chronic periodontitis; diabetes mellitus; non-surgicalperiodontal therapy; Biomarkers; Periodontitis; biomarker; N-Acetylneuraminic Acid; Female; mužské pohlaví; Adult; Middle Aged; diabetes mellitus 2. typu; Diabetes Complications; komplikace diabetu; Humans; parodontitida; kyselina N-acetylneuraminová; biologické markery; dospělí; Male; acute phase proteins